الـتأطير القانوني لمكافحة ظاهرة الجريمة واتساعها في المجتمع (2020-2024) محافظة السليمانية أنموذجا - fatah, Dalia Sherko shakir; Omer, Aeda Abdulkareem Saleh (Journal of Legal and Political Studies, 2025)
Crimes pose a threat to the fabric of societies and their interests in general , and specifically in the Kurdish society in the Kurdistan Region , which requires research and study, especially after the increase in the percentage of crimes committed in Sulaymaniyah Governorate, which has become a tangible phenomenon worthy of study .such research has become necessary for the reader to look at the most prominent factors behind the occurrence of this phenomenon , to prove that there is a grope of reasons and motives, some of which are general to cause crimes everywhere without specifying, but there are special ones that cause the spread and recurrence of certain crimes in themselves within the scope of Sulaymaniyah Governorate, and this is what was proven by official statistics, international reports and the opinions of experts and specialists in various fields related to the research topic ,and such reasons and motives can be curbed by following legal , academic and realistic methods in institutions concerned with crime and combating it .
Keywords: Keywords Crime motives; causes of crime; crime phenomenon; psychological causes; drugs